Assessing Awareness, Attitude, and Practices of Breast Cancer Screening and Prevention Among General Public and Physicians in Pakistan: A Nation With the Highest Breast Cancer Incidence in Asia - Adeel Aslam; Asma Ghulam Mustafa; Ali Hussnain; Hafsa Saeed; Fatima Nazar; Maha Amjad; Ayesha Mahmood; Atika Afzal; Anam Fatima; Doaa Kamal Alkhalidi (International Journal of Breast Cancer)
Conclusion: In conclusion, breast cancer awareness among the general public is limited, highlighting the need for tailored education programs. Although most physicians show high awareness, challenges in patient communication and barriers, such as fear and financial constraints, must be addressed to improve screening uptake. These findings emphasize the importance of targeted interventions to enhance public awareness, screening practices, and physician-patient communication.